Exploring pharmacy students’ comfort levels with peer-conducted blood pressure examinations - Fahamina Ahmed; Meva Beganovic; Fatima Zeini; Candice Smith; Amne Borghol (Discover Education)
Abstract Introduction Various methods are used to assess healthcare professional students’ physical exam skills. Hypertension is a common chronic disease that affects nearly half of adults in the United States, therefore measuring blood pressure is a clinical skill often assessed in a healthcare program curriculum. Methods This study was conducted to collect data and analyze certain characteristics regarding the views of second year pharmacy students having their blood pressure assessed by their classmates in a hypertension skills lab. These views were collected using Qualtrics™, a voluntary, anonymous electronic survey. Results Eighty-five respondents (~ 82% response rate) were included in this survey analysis. Majority of the students were between the age of 18–24 years (75%), female (79%), and African American (56%). Most students reported feeling comfortable (82%) having their blood pressure assessed by their peer, with no significant difference when considering racial/ethnic groups, age, gender, or family history. Conclusions Although there was no statistical significance found amongst most analyses, these outcomes displayed awareness into a subject that may need to be further explored. Since numerous factors can vary between the student and examiner, comfort levels and personal preferences should be of importance.